Oxidation of Renewables - Behr, Arno; Vorholt, Andreas J (Homogeneous Catalysis with Renewables, 2017)
Oxygen, one of the most essential elements in nature, plays a key role in chemistry since many chemical structures get their defined functionality through the presence of O-heteroatoms; examples include alcohols, ethers, carbonyl compounds, and most importantly epoxides.